How can sexual and reproductive health and rights be enhanced for young people with intellectual disability? - focus group interviews with staff in Sweden - Maria Wickström; Margareta Larsson; Berit Höglund (BMC, 2020)
Abstract Background Different types of staff support individuals with intellectual disability (ID) in their daily life, in schools, leisure activities and in special accommodations. This study aimed to gain a deeper understanding of experiences and perceptions regarding sexual and reproductive health and rights (SRHR) among staff. Methods Data were collected in mid-Sweden in four focus groups with altogether 20 participants, 18 women and 2 men aged between 18 and 65 years. They had different professions and worked among youth and adults with ID aged 18-40 years in schools, accommodations and with leisure activities. Their working experience varied from 3 years to more than 20 years. Interviews were audio recorded, transcribed and analysed with content analysis. Results The participants generally described positive attitudes towards sexuality for people with ID, both among themselves and in society. However, many situations such as ensuring privacy, balancing between waiting and acting, issues around contraception and reproduction were difficult to address and participants had hesitations about childbearing. They described different strategies such as showing respect, enhancing self-esteem and decision making ability and using interprofessional support to cope with frustrating situations. They lacked a clear mandate from managers as well as written guidelines and policies. They requested education and support from peers, supervisors and other professionals. Conclusion Participants in the study were generally open-minded and accepting towards sexuality among young people with ID. They thought it was difficult to deal with reproduction/parenthood and felt unprepared and frustrated in certain situations. The participants requested a clear mandate from managers, organizational guidelines, more education and inter-professional support. We believe these findings can inform the development of policy and support the implementation of SRHR related guidelines to support staff working with young people with ID.